On the Stylistic Evolution of Domed Structures in the Early 18th Century Russian Architecture - Ukhnalev, Andrei E. (Actual Problems of Theory and History of Art, 2018)
In terms of Russian architecture, the early 18th century saw a number of designs and constructions developing the concept of a Renaissance centrally planned temple. This paper deals with such designs as J.- N. Delisle’s Kunstkamera tower, T. Schwertfeger’s church “Sad Petrov”, P. A. Trezzini’s cathedral in the Monastery of St. Sergius, and the implemented design of the Nativity of the Blessed Virgin Mary in the village of Podmoklovo near Moscow. The paper gives an in-depth look into the architectural context that was behind these designs, defining their style. The array of the prototypes for these works is not limited to C. Fontana’s project for the Church in Honour of the “Ecclesia Triumphans”, which has been noted by other researchers, but includes specimens of “paper architecture” created in the Academy of Saint Luke and the French Academy in Rome alongside with a piece of French Renaissance architecture. The relationship between the model and the actual piece of work is sometimes definite. However, it is only the concept that is borrowed; it is then subjected to liberal revision. Besides, the new interpretation is often based on something other than artistic considerations. In the projects in question, the style assumes a noticeably evolutionary character. It involves a gradual increase in the use of baroque components: from the designs that led researchers to misinterpret the important milestone in architecture — the church in Podmoklovo — as a protoclassicist piece, to the excessive recognition of baroque potential in P. A. Trezzini’s cathedral project.